Sentiment Analysis using different techniques - Preeti,Priyanka Bhardwaj,Rajwant Kaur (International Journal of Advanced Science and Technology, 2020)
Sentiment analysis is an application of natural language processing (NLP). It is also known as opinion mining or emotion extraction. Sentiment analysis is an ongoing research field in text mining. The main objective is to identify the polarity of the text and categorize it into positive, negative or neutral. It helps us to better understand the human decision making. It can also be used for identifying and analyzing the sentiments from comments or reviews on the various blogs, web sites, social media, online communities and others in order to understand the opinions of consumers. In order to perform sentiment analysis, various tasks such as subjectivity detection, sentiment classification, feature extraction, aspect term extraction, have to be performed. The different algorithms used for sentiment analysis are delineated in this paper.